Pasar Modal dan Penanaman Modal Asing di Indonesia - Poppy Camenia Jamil; Restu Hayati (COSTING : Journal of Economic, Business and Accounting, 2021)
The role of the capital market for the economy of a country according to capital market education by PT. There are two functions of the Indonesia Stock Exchange, namely as a means of business funding or as a means for companies to obtain funds from investors (investors) for business development, expansion, additional working capital and others. This study aims to explain the relationship between the capital market and foreign investment in Indonesia. The variables used in this study are the return of the Composite Stock Price Index (IHSG) and Foreign Direct Investment (FDI) from 2003 to 2019. Data analysis techniques use regression analysis to explain the relationship between the capital market and foreign investment in Indonesia. Indonesia. The final results of the achievements in this study are to increase literacy understanding about economic activities, capital markets, investment to contribute to economic growth. Keywords: IHSG, FDI, Investment, Capital Market, Stock Index.